Untargeted Metabolomics and Bioactivities Assessment of Xylaria ellisii, an Endophytic Fungus Isolated from the Leaf of the Plant Acorus calamus Linn. - Prajapati, Chandrabhan; Rai, Sachchida Nand; Singh, Anurag Kumar; Rajak, Naina; Garg, Neha; Singh, Santosh Kumar (Current Pharmaceutical Design, 2025)
IntroductionFungal endophytes have mutualistic associations with the plant's host, communicating through genetic and metabolic processes. As a result, they gain the ability to generate therapeutically effective metabolites and their derivatives.MethodsThe current study aims to assess antioxidant potential along with the identification of robust metabolites within the crude extract of a potent endophytic fungus Xylaria ellisii isolated from leaf tissues of the Acorus calamus Linn. plant. Four endophytic fungi were obtained from leaf tissues of Acorus calamus Linn., and identified morphologically and molecularly as distinct species. Each ethyl acetate extract of the isolated fungi exhibited a unique chemical profile in the HPTLC fingerprint at various wavelengths. The ethyl acetate (EA) extract from the fungal strain ACL-4 (Xylaria ellisii) demonstrated the strongest antioxidant activity among the four fungal endophytes examined, with an EC50 value of 292.64 ± 3.558 µg/mL. Remarkably, fungal endophyte ACL-4 extract exhibited superior antimicrobial activity at the less concentrations compared to ACL-ME extract of leaf crude.ResultsThe extract of ACL-ME-treated HEK 293T cells exhibited significant toxicity, with an IC50 value of 1481.74 ± 23.772 µg/mL, compared to fungal strain ACL-4-treated HEK 293T cells, which had an IC50 value greater than 2000 µg/mL. Consequently, the crude extract of ACL-4 and ACL-ME along with the standard drug methotrexate exhibited cytotoxic activity against cancer cell line MDA-MB-231 with IC50 concentrations of 146.65 ± 0.394 µg/mL, 528.46 ± 10.912 µg/mL, and 134.11 ± 3.446 µg/mL, respectively. A total of 2,255 compounds were detected through LC-HRMS-based metabolomics in the crude metabolites of Xylaria ellisii, with certain compounds identified in multiple instances. Among this repertoire, 62 robust bioactive compounds were identified through meticulous screening, guided by existing literature. Comparative HPTLC fingerprint analysis, along with antioxidant efficacy assays of ethyl acetate extracts of Xylaria ellisii derived from Acorus calamus leaves and Cassia fistula twigs revealed the host-specific production of bioactive chemicals.ConclusionThe top-scoring Keap1 inhibitors derived from Xylaria ellisii, including Pregabalin (-6.083 Kcal/mol), Ferulic acid (-5.434 Kcal/mol), (R)-Piperidine-2-carboxylic acid (-5.31 Kcal/mol), Genipin (-5.197 Kcal/mol), and Brivaracetam (-5.17 Kcal/mol), respectively were considered as Keap 1 inhibitors, potentially mitigate oxidative stress.
Keywords: LCHRMS